Coating method and resulting ceramic modified separator

By combining the drying technology of flotation oven and tenter method, the problem of edge effect of microporous polyolefin membranes in conventional flotation ovens and pore collapse at high temperatures is solved, and efficient production and dimensional stability of membranes are achieved.

CN119790538APending Publication Date: 2025-04-08AMTEK RESEARCH INTERNATIONAL LLC
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202380062730.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-23
Filing Date
2023-09-22
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

The prior art, when using conventional flotation ovens, leads to edge effects of microporous polyolefin films, reducing yields, and pores of the film may collapse at high temperatures, affecting permeability.

Method used

Using a drying technology combining flotation oven and tenter method, the film is restricted in the transverse direction by interlaced air knives, drying and trimming damaged edges at high temperatures, while improving production efficiency.

Benefits of technology

Overcome the edge effect, improve yield and productivity, ensuring that the membrane maintains good in-plane dimensional stability and low shrinkage at high temperatures.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119790538A_ABST
    Figure CN119790538A_ABST
Patent Text Reader

Abstract

The present disclosure relates to a continuous process for coating a microporous polyolefin web with a ceramic composition or slurry, followed by drying at an elevated temperature while confining in a transverse direction. Such nets may be used to improve manufacturability, performance, and safety of energy storage devices, such as lithium batteries.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] Related Applications

[0002] This application claims priority to U.S. Provisional Patent Application No. 63 / 376,952, filed on September 23, 2022, and entitled COATING METHOD AND RESULTANT CERAMIC-MODIFIED SEPARATORS, which is incorporated herein by reference in its entirety.

[0003] Copyright Notice

[0004] ©2023 Amtek Research International LLC. A portion of the disclosure of this patent document contains material that is subject to copyright protection. The copyright owner has no objection to the facsimile reproduction by anyone of the patent document or the patent disclosure, as it appears in the Patent and Trademark Office patent files or records, but otherwise reserves all copyright rights whatsoever. 37 CFR §1.71(d). Technical Field

[0005] The present invention relates to a continuous process for coating a microporous polyolefin membrane with a ceramic composition or slurry, followed by drying at high temperature while restraining in the transverse direction, trimming damaged edges, and winding into a finished coil. The improvements are (1) the ability to overcome edge effects that cause defects and reduced yields when using conventional flotation ovens, and (2) faster line speeds compared to stenter frames used in the textile industry due to staggered air knives. The resulting membrane exhibits good in-plane dimensional stability (i.e., low shrinkage) at both temperatures above and below the melting point of the polyolefin matrix. At high temperatures (>135°C), pores within the bulk structure of the membrane may begin to collapse or close, thereby changing the permeability through the membrane, while the in-plane dimensional changes are small. Such membranes can be used to improve the manufacturability, performance, and safety of energy storage devices such as lithium batteries. Throughout this application, the term "lithium battery" refers to batteries based on Li ions and / or rechargeable Li metal. Background of the Invention

[0007] The separator is an integral part of the performance, safety and cost of lithium-ion batteries. During normal operation, the main function of the separator is to prevent electronic conduction (i.e., short circuit or direct contact) between the anode and the cathode while allowing ionic conduction via the electrolyte. For small commercial battery cells under abuse conditions (such as external short circuit or overcharge), the separator is required to be closed at a temperature far below that at which thermal runaway may occur. Closure is caused by the collapse of pores in the separator due to the melting and viscous flow of the polymer, thereby slowing down or preventing the flow of ions between the electrodes. Almost all Li-ion battery separators contain polyethylene as part of a single or multilayer construction, so that closure begins at about 130°C (i.e., close to the melting point of polyethylene).

[0008] Separators for the lithium-ion battery market are currently manufactured via either a "dry" or "wet" process. Celgard LLC and others have described a dry process in which polypropylene (PP) or polyethylene (PE) is extruded into a thin sheet and subjected to rapid drawing. The sheet is then annealed at 10°C-25°C below the melting point of the polymer so that the crystallite size and orientation are controlled. Next, the sheet is rapidly stretched in the machine direction (MD) to achieve slit-like pores or voids. Three-layer PP / PE / PP separators produced by the dry process are commonly used in lithium-ion rechargeable batteries.

[0009] Wet-process diaphragms composed of high molecular weight polyethylene are produced by the following steps: extrusion of a plasticizer / polymer mixture at high temperature, followed by phase separation, biaxial stretching, and extraction of a pore former (i.e., plasticizer). The resulting diaphragm has elliptical or spherical pores that have good mechanical properties in both the machine and transverse directions. PE-based diaphragms manufactured in this manner by Toray, Asahi, SEM Corp, and ENTEK have found widespread use in Li-ion batteries.

[0010] In the case of large format or higher capacity Li-ion battery cells designed for electric vehicles, the benefits of membrane closure have been questioned because it is difficult to ensure sufficient rate and uniformity of closure throughout the battery cell. As such, many companies have focused on changing the construction of lithium-ion battery cells to include (1) a heat-resistant separator or (2) a heat-resistant layer coated on an electrode or conventional polyolefin separator. Heat-resistant separators composed of high temperature polymers (e.g., polyimide) have been produced on a limited basis from solution casting, electrospinning, or other process techniques. In these cases, the high polymer melting point prevents closure at temperatures below 200°C.

[0011] In U.S. Pat. No. 9,896,555 B2, ENTEK describes a free-standing microporous ultra-high molecular weight polyethylene (UHMWPE)-based membrane containing sufficient inorganic filler particles to provide low shrinkage while maintaining high porosity at temperatures above the melting point of the polymer matrix (>135° C.) Such free-standing heat-resistant membranes have excellent wettability and ultra-low impedance, but due to the high loading level of the inorganic filler, they do not exhibit closed-cell properties.

[0012] In U.S. Pat. No. 7,638,230B2, a porous heat-resistant layer is applied to the negative electrode. The heat-resistant layer is composed of an inorganic filler and a polymer binder. The inorganic filler includes magnesium oxide, titanium dioxide, zirconium oxide, or silicon dioxide. The polymer binder includes a modified rubber mixture of polyvinylidene fluoride and acrylonitrile units. The heat-resistant layer contains 1-5 parts of binder per 100 parts by weight of inorganic filler. Higher binder content will negatively affect the high rate discharge characteristics of the battery. In addition, the thickness of the porous heat-resistant layer must be limited to 1-10um to obtain a high discharge rate, and it cannot be removed as a free-standing film. Free-standing means that the sheet has sufficient mechanical properties so that operations such as winding and unwinding in film form can be used during assembly of the energy storage device.

[0013] In U.S. Patent Application Publication No. 2008 / 0292968A1 and U.S. Patent Application Publication No. 2009 / 0111025A1, an organic / inorganic separator is disclosed, wherein a porous substrate is coated with a mixture of inorganic particles and a polymer binder to form an active layer on at least one surface of the porous substrate. The porous substrate can be a nonwoven fabric, a film, or a polyolefin-based separator. The inorganic particles are selected from the group consisting of those exhibiting a dielectric constant greater than 5, piezoelectricity, and / or lithium ion conductivity. A variety of polymer binders are described. Compared with uncoated polyolefin-based separators used in lithium batteries, it is said that the composite separators show excellent thermal safety, dimensional stability, electrochemical safety, and lithium ion conductivity. In the case of certain polymer binders mixed with inorganic particles, the electrolyte may cause a high degree of swelling in the surface layer, but rapid wetting or swelling is not achieved in the polyolefin substrate.

[0014] In the case of applying a ceramic composition or slurry to a microporous polymer matrix or polyolefin web and subsequently drying to form a lithium ion separator having high temperature dimensional stability and improved oxidation resistance while in contact with a high voltage cathode, there is a need to reduce costs through higher throughput and improved yields. In many cases, the rate-limiting steps include web handling and drying through a flotation oven or a conventional hot air oven. When only one side of the polyolefin web is first coated, followed by a secondary unwinding and coating step to coat the other (second) surface of the web, improvements in yield and throughput become even more difficult.

[0015] Heretofore, consideration has not been given to combining the benefits from a tenter frame (where, typically, a liquid saturated fabric is held under tension in the cross direction with pins or clips as it traverses a conventional hot air oven) with high speed air knives used in flotation ovens for drying. In the present invention, we have discovered that such a combination is a cost effective method for drying polyolefin webs that have had ceramic compositions or slurries applied to both surfaces of the web. SUMMARY OF THE INVENTION

[0017] The object of the present invention is to achieve thin, free-standing, microporous polyolefin membranes having good oxidation resistance and high temperature dimensional stability as provided by a porous ceramic layer applied to one or both surfaces of a web or polymer substrate. "Free-standing" means that the web or membrane has sufficient mechanical properties for unwinding, coating, winding, cutting and other web handling operations. The terms "membrane", "sheet", "substrate", "web" and "membrane" can be used interchangeably, and the term membrane can be used to cover webs, membranes, substrates and sheets.

[0018] There are a wide variety of drying and curing ovens that are commonly used for coating and roll-to-roll processing of plastic films, papers, or foils. Such ovens may include roller supports or belt / conveyor supports for single-sided coating of such substrates. In the case of double-sided coating, the web cannot contact the support rollers before being completely dried. This is the case where flotation ovens have been best utilized, particularly in the case of double-sided ceramic slurry coatings of microporous polyolefin webs for use as separators in lithium batteries.

[0019] Figure 1 A side view of an open flotation oven is shown in FIG. 1 (depicting an exemplary flotation oven with staggered air knives 10). When using such an oven, it is expected that the double-sided coated plastic film, paper, or foil follows the sinusoidal pattern established by the air knives as it traverses the oven. At the same time, the liquid carrier (e.g., water or an organic solvent) from the coating solution is evaporated and removed from the surface of the plastic film, paper, or foil. An advantage of a flotation oven is the ability to adjust the air velocity and air knife geometry so that rapid drying can be achieved. In the case of porous materials such as paper, there are also capillary forces exerted within the pores that cause stress and shrinkage during the drying process.

[0020] In the case of microporous polyolefin webs, special precautions must be taken due to their thickness (<20-25 um) and porosity, which results in a lower modulus (i.e. stiffness) than conventional PET films (about 100 um) that are usually coated and dried in such ovens. Furthermore, the distance between the top of the air knife and the microporous polyolefin web traveling through the oven, as well as the associated air velocity, needs to be re-established for each different thickness not only of the web but also of the applied thickness of the coating solution in its wet state ("wet" thickness).

[0021] An additional challenge with flotation ovens is the edge effect, which is created by the "baggy edges" in the master roll of the microporous polyolefin web as it is unwound and passes through the coating station before entering the flotation oven. The "baggy edges" make it difficult to establish a uniform sinusoidal pattern from the air knife even without applying a coating. This effect is exacerbated once the coating solution is applied and creates defects if the coated web contacts the air knife, leaving ceramic deposits and uncoated areas on the web. The coated edge may also curl due to uneven deposition of the coating solution at the edge.

[0022] As thin microporous polyolefin webs become wider, edge effects and other potential defects become even more prevalent. This is because the tendency to form creases in the machine direction increases. As such, most flotation ovens used to produce ceramic coated polyolefin membranes do not exceed 1.2 meters in width.

[0023] To overcome the above challenges, ENTEK has combined the flotation oven design with the tenter frame method used in the textile industry. In the tenter frame method, the saturated fabric is held in the cross direction with pins (needles) or clips while the material traverses a hot air oven where convection is used for drying. Figure 2 A schematic diagram of an exemplary tenter frame is shown in FIG. 5 (depicting a fabric (to which chemicals have been applied) being held in the cross-machine direction via a chain of pins or needles as the fabric passes through an oven or dryer).

[0024] The present invention is a microporous, free-standing, heat-resistant polyolefin membrane produced by applying a ceramic composition or slurry to one or both major surfaces, followed by drying with an air knife impinging on the membrane while restraining the membrane in the transverse direction (e.g. Figure 3 ). Lateral confinement helps minimize capillary forces that typically cause shrinkage or pore collapse during solvent evaporation. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 A schematic diagram of an exemplary flotation oven is depicted.

[0026] Figure 2 A schematic diagram of an exemplary tenter frame is depicted.

[0027] Figure 3 Depicted is a schematic diagram of an exemplary drying oven according to embodiments of the present disclosure. DETAILED DESCRIPTION

[0028] The microporous membrane used in the present invention is composed of a polyolefin polymer matrix or bulk structure. The polyolefin most preferably used in the polyolefin matrix is ​​a very high molecular weight polyethylene (VHMWPE) having an Mw greater than about 300,000 g / mol (e.g., about 300,000 to about 3.1 million grams / mol). In some cases, it is desirable to blend VHMWPE with other polyolefins such as ultra-high molecular weight polyethylene (UHMWPE, Mw greater than about 3.1 to about 10 million grams / mol), high density polyethylene (HDPE) or linear low density polyethylene (LLDPE) to affect features such as closed cells or melting characteristics of the membrane. Microporous membranes typically include a porosity of about 35%-65%. The pore size range is typically about 10 nanometers to several microns, with an average pore size of less than about 1 micron. The thickness of the membrane (excluding the coating) is typically about 3-25 μm, or about 20 μm or less.

[0029] The ceramic coating formulation used in the present invention includes inorganic particles dispersed in an aqueous mixture, which may contain a small amount of alcohol to improve the wettability of the polyolefin film surface. Exemplary inorganic particles that can be used include inorganic oxides, carbonates, or hydroxides, such as at least one of aluminum oxide, silicon dioxide, zirconium oxide, titanium dioxide, mica, boehmite, magnesium hydroxide, calcium carbonate, another suitable inorganic acid, or a mixture thereof. One or more hydrotalcites can also be used alone or in combination with another type of inorganic particles. The inorganic particles are typically charge-stabilized and remain suspended in the aqueous mixture. Low molecular weight water-soluble polymers or polymer dispersions are typically used as binders for inorganic particles. It is desirable to select a polymer with many hydrogen bonding sites so as to minimize the binder concentration, but to achieve a robust microporous surface film that is not easy to fall off the inorganic particles. Acrylates, polyvinyl pyrrolidone, polyvinyl alcohol, carboxymethyl cellulose and copolymers or derivatives thereof are preferred representatives of polymer binders, so that less than or equal to 10 parts of the polymer binder can be used with 90 parts or more of the inorganic particles.

[0030] In another embodiment, a binder layer comprising an acrylate or polyvinylidene fluoride (PVDF) copolymer may be disposed on the ceramic layer to form a four-layer or five-layer structure. As will be appreciated, the four-layer structure may include a polyolefin layer coated with a ceramic layer on one main surface, followed by each main surface of the polyolefin / ceramic structure coated with a binder layer. The five-layer structure may include a polyolefin layer coated with a ceramic layer on two main surfaces, followed by each main surface of the ceramic layer coated with a binder layer. In another embodiment, an acrylate or polyvinylidene fluoride (PVDF) copolymer may be combined with inorganic particles so that the double-sided coated diaphragm may then adhere to the battery electrode under heat and pressure.

[0031] In addition to controlling the amount of polymer binder and inorganic particles in the ceramic coating formulation, we have found that controlling the particle size distribution of the inorganic particles is important. In addition, the coating formulation must be carefully applied to the polyolefin web in order to control the thickness of the resulting surface layer. Coating methods include dip coating, micro-gravure printing, gravure printing, spraying, slot die, and other methods that can achieve the correct "wet" thickness before drying. The preferred drying method utilizes an air knife 20 in combination with a pin or clamp system 30 that holds the web 40 and maintains its extension in the transverse direction as the web moves through an oven and then is subsequently wound into a coil, such as Figure 3 The air knife 20 can be aligned (as shown in Figure 3 ), or they may be staggered. Under such a drying system, the width of the polyolefin web 40 passing through the dryer or oven may be greater than about 1.2 m (e.g., such as about 1.2 m to about 2.4 m or more). The temperature of the dryer or oven may be about 60° C. to about 135° C., about 80° C. to about 130° C., or about 125° C. or higher. After drying, the coating weight on the film may be about 0.3 g / m 2 About 12g / m 2 , about 1g / m 2 About 8g / m 2 , or about 4g / m 2 About 6g / m 2 The coated film may also exhibit a Gurley value of about 30 to about 250 seconds / 100 cc of air, or about 100 to about 200 seconds / 100 cc of air.

[0032] Example 1

[0033] A microporous polyethylene film (ENTEK 12EPH; 12.4 um; 49.6% porosity; Gurley air permeability = 104 sec / 100 cc air) was unwound under controlled tension and passed through a carbon composite roller to a horizontal position, at which time the top film surface was coated with a 20 wt.% solid aqueous ceramic slurry (97 / 3 fumed alumina / PVOH) (which contained 4 wt% isopropyl alcohol to improve wettability) using a Mayer rod #10. The solution was coated over the entire width of the sheet except for the outer approximately 40 mm on each side, which was then held in clamps on a chain system. The chains holding each side of the web were parallel over the entire distance of the oven, which had top and bottom staggered air knives at a distance of approximately 100 mm from each surface of the polyethylene film. The wetted film was advanced through the oven at 20 m / min with an oven temperature of 125°C in a plenum feeding the air knives.

[0034] For the single-sided ceramic-coated membrane, the coating weight was determined to be approximately 1.1 g / m 2The thickness was about 14.4 um, and the air permeability was measured to be 96 sec / 100 cc air, which is unexpectedly lower than the uncoated polyethylene film.

[0035] Example 2

[0036] A microporous polyethylene film (ENTEK 12EPH; 12.4 um; 49.6% porosity; Gurley air permeability = 104 sec / 100 cc air) was unwound under controlled tension and passed through a carbon composite roller to a horizontal position, at which time the top film surface was coated with a 20 wt.% solid aqueous ceramic slurry (97 / 3 fumed alumina / PVOH) (which contained 4 wt% isopropyl alcohol to improve wettability) using a Mayer rod #10. The solution was coated over the entire width of the sheet except for the outer approximately 40 mm on each side, which was then held in clamps on a chain system. The chains holding each side of the web were parallel over the entire distance of the oven, which had top and bottom staggered air knives at a distance of approximately 100 mm from each surface of the polyethylene film. The wetted film was advanced through the oven at 20 m / min with an oven temperature of 135°C in a plenum feeding the air knives.

[0037] Even at this higher dryer temperature (close to the peak melting point of polyethylene), the single-sided ceramic-coated film had a 1.25 g / m 2 The coating weight was 2.33 W and the Gurley value was 96 seconds / 100 cc of air.

[0038] It will be understood that references throughout this specification to "one (an) embodiment" or "the (the) embodiment" mean that a particular feature, structure or characteristic described in connection with the embodiment is included in at least one embodiment. Therefore, reference phrases, or variations thereof, as described throughout this specification are not necessarily all referring to the same embodiment.

[0039] Similarly, it should be understood that in the above description of the embodiments, various features are sometimes grouped together in a single embodiment, figure, or description thereof for the purpose of simplifying the present disclosure. However, this method of disclosure should not be interpreted as reflecting the following intention: any claim requires more features than those explicitly listed in the claim. On the contrary, as reflected in the following claims, various aspects of the present invention lie in fewer combinations than all the features of any single previously disclosed embodiment. Therefore, the claims following this specific embodiment are hereby expressly incorporated into this specific embodiment, with each claim representing a separate embodiment on its own. This disclosure includes all permutations of independent claims and their dependent claims. In addition, additional embodiments that can be derived from the following independent and dependent claims are also expressly incorporated into this written description.

[0040] Recitation of the term "first" with respect to a feature or element in the claims does not necessarily imply the presence of second or additional such features or elements.

[0041] Throughout this specification, reference is made to approximate values, such as by using the term "about". For each such reference, it is understood that in some embodiments, a value, feature, or characteristic may be specified without the approximate value. For example, where a qualifier such as "about" is used, the term includes the qualified term within its scope when it is absent its qualifier. For example, where the term "about" is described with respect to a feature, it is understood that in other embodiments, the feature may have a precise configuration. Unless otherwise indicated, all ranges include endpoints and all numbers between the endpoints.

[0042] Without further elaboration, it is believed that those skilled in the art can use the previous description to maximize the use of the present invention. The claims and embodiments disclosed herein are interpreted as being merely illustrative and exemplary and do not limit the scope of the present disclosure in any way. It will be apparent to those of ordinary skill in the art that, with the aid of this disclosure, the details of the above-described embodiments may be changed without departing from the basic principles disclosed herein. In other words, various modifications and improvements of the embodiments specifically disclosed in the above description are within the scope of the appended claims. In addition, without departing from the scope of the present disclosure, those skilled in the art may change the order of the steps or actions of the methods disclosed herein. In other words, unless a specific order of steps or actions is required for the proper operation of the embodiment, the order or use of specific steps or actions may be modified. Therefore, the scope of the present invention is defined by the following claims and their equivalents.

Claims

1. A freestanding microporous membrane comprising: a polymer matrix extending from one surface to an opposite surface, the polymer matrix comprising a polyolefin having a molecular weight of 300,000 g / mol or greater; as well as A porous ceramic coating is disposed on at least one side of the polymer substrate, wherein the microporous membrane is formed in a continuous process in which the ceramic coating is dried while the polymer substrate is restrained in a lateral direction at an elevated temperature.

2. The microporous membrane according to claim 1, wherein The polymer matrix includes a blend of very high molecular weight polyethylene (VHMWPE) and at least one of ultra high molecular weight polyethylene (UHMWPE), high density polyethylene (HDPE), or linear low density polyethylene (LLDPE).

3. The microporous membrane according to claim 1 or claim 2, wherein: The polymer matrix comprises a thickness of about 20 μm or less.

4. A microporous membrane as claimed in any one of the preceding claims, wherein The polymer matrix includes a width of about 1.2 m or greater.

5. A microporous membrane as claimed in any one of the preceding claims, wherein The porous ceramic coating is disposed on two opposing sides of the polymer substrate.

6. A microporous membrane as claimed in any one of the preceding claims, wherein The film has a g / m 2 , about 1 to about 8 g / m 2 , or from about 4 to about 6 g / m 2 coating weight.

7. A microporous membrane as claimed in any one of the preceding claims, wherein The film exhibits a Gurley value of about 30 to about 250 seconds / 100 cc of air, or about 100 to about 200 seconds / 100 cc of air.

8. A microporous membrane as claimed in any one of the preceding claims for use as a ceramic modified separator in a lithium ion or rechargeable Li metal battery.

9. A method for making a freestanding microporous membrane, the method comprising: confining a polymer matrix in a transverse direction thereof, the polymer matrix comprising a polyolefin having a molecular weight of 300,000 g / mol or more; coating at least a portion of at least one side of the polymer substrate with a ceramic coating; as well as The polymer matrix and the ceramic coating are exposed to an elevated temperature.

10. The method of claim 9, wherein: Constraining the polymer matrix includes constraining the polymer matrix with pins or clamps.

11. The method according to any one of claims 9 or 10, wherein: Exposing the polymer matrix and the ceramic coating to an elevated temperature includes exposing the polymer matrix and the ceramic coating to a temperature of about 125° C. or greater.

12. The method according to any one of claims 9 to 11, wherein: Exposing the polymer matrix and the ceramic coating to an elevated temperature includes placing the polymer matrix and the ceramic coating in a drying oven.

13. The method according to any one of claims 9 to 12, wherein: The polymer matrix comprises a thickness of about 20 μm or less.

14. The method according to any one of claims 9 to 13, wherein: The polymer matrix includes a width of about 1.2 m or greater.

15. The method according to any one of claims 9 to 14, wherein: The polymer matrix includes a blend of very high molecular weight polyethylene (VHMWPE) and at least one of ultra high molecular weight polyethylene (UHMWPE), high density polyethylene (HDPE), or linear low density polyethylene (LLDPE).

16. The method according to any one of claims 9 to 15, wherein: The ceramic coating is on two opposing sides of the polymer substrate.

17. The method according to any one of claims 9 to 16, wherein: The film has a g / m 2 , about 1 to about 8 g / m 2 , or from about 4 to about 6 g / m 2 coating weight.

18. The method according to any one of claims 9 to 17, wherein: The film exhibits a Gurley value of about 30 to about 250 seconds / 100 cc of air, or about 100 to about 200 seconds / 100 cc of air.

19. A freestanding microporous membrane formed according to the method of any one of claims 9 to 18.

20. A drying oven, comprising: Entrance; an outlet downstream of the inlet; a passage extending between the inlet and the outlet; a plurality of air knives placed in the passage; as well as A plurality of restraining elements are configured to restrain the polyolefin web in a lateral direction thereof as the polyolefin web moves from the inlet to the outlet.

Citation Information

Patent Citations

  • Organic / Inorganic Composite Separator Having Morphology Gradient, Manufacturing Method Thereof and Electrochemical Device Containing the Same

    US20080292968A1

  • Organic / inorganic composite microporous membrane and electrochemical device prepared thereby

    US20090111025A1

  • Lithium ion secondary battery

    US7638230B2

  • Freestanding, heat resistant microporous film for use in energy storage devices

    US9896555B2